Mapping drought prone areas using the weight overlay method in Serang Regency - Sania, Annidatus; Ruhiat, Yayat; Denny, Yus Rama (Universitas Muhammadiyah Mataram, 2025)
This research aims to analyse or estimate drought vulnerability in Serang Regency. The background of this research is based on areas that often experience moderate and even high levels of drought. The research method used is quantitative by using rainfall parameters, soil type parameters, and land use parameters which are then put together using the overlay method to obtain drought vulnerability areas in Serang Regency. Based on the results of the research, there are areas with low, medium, and high levels of drought vulnerability. The area with the largest drought vulnerability in Serang Regency is at the medium level of vulnerability. The results of the map analysis of the level of drought vulnerability indicate that there is a relationship between each parameter, with most of the drought vulnerability being influenced by several factors, including rainfall, soil type, and land use.